Cultural Materialism in Lorca’s Poetry - Soqandi, Mahnaz; Basirizadeh, Fatemeh Sadat (Budapest International Research and Critics University, 2020)
The aim of the present research is to investigate Lorca’s poem from cultural materialist point of view. To do so, the researcher investigates how culture and social mechanism function in the context in which the poems have been written. Cultural materialism attempts to investigate different aspects of society, art, economy, language, and politics from an external point of view and analyze them to find out how identity and self are shaped accordingly. Cultural materialism is demonstrated in different categories including gender, ethnic studies, postmodernism, postcolonialism, and other fields. Cultural materialism highlights the relation between a work of art and the ideological system in which it has been created. In other words, cultural, social, religious and several other factors must be accounted for while interpreting a work of art. Consequently, how cultural dogma functions within fine arts in order to produce the internal textures is uncovered through cultural materialism. In Lorca’s poems, the contents have symbolic and metaphoric mechanisms which can be interpreted through material analysis.